1988
DOI: 10.1007/bf02371540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental conditions on the fixation and transfer of nitrogen from alfalfa to associated timothy

Abstract: Nitrogen fixation (NF) by alfalfa and nitrogen transfer (NT) from alfalfa to associated timothy was studied under different environmental conditions in controlled growth chambers, using the ~N dilution technique. Evidence was obtained of NT from alfalfa to the associated timothy. Conditions that favored NF by alfalfa resulted in an increase in its NT. Of 3 different temperature regimes (25/20, 16/14, and 12/9~ day/night), 16-25/14-20~ was the best range for NF by alfalfa and resulted in the greatest NT. High l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…This observation supports our previous finding which showed that treatments such as defoliation, pod removal and stem girdling which caused a decline in dinitrogen fixation in soybean did not change the amount of nitrogenous compounds exuded by the root systems except for stem girdling. As a result we could not confirm an earlier report (Ta and Faris 1988) indicating the presence of a direct relationship between the conditions which favor N fixation and N transfer in alfalfa. Further studies should be carried out to examine the relationship between dinitrogen fixation and the release of nitrogenous compounds from the root system of legumes.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation supports our previous finding which showed that treatments such as defoliation, pod removal and stem girdling which caused a decline in dinitrogen fixation in soybean did not change the amount of nitrogenous compounds exuded by the root systems except for stem girdling. As a result we could not confirm an earlier report (Ta and Faris 1988) indicating the presence of a direct relationship between the conditions which favor N fixation and N transfer in alfalfa. Further studies should be carried out to examine the relationship between dinitrogen fixation and the release of nitrogenous compounds from the root system of legumes.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the 15N content of the grass in the mixture is lower than that of the grass monoculture, it seems likely that the additional source of N is at, or near, natural abundance (0.366at.% and is derived from N fixed by the legume. This could involve direct transfer of N (Eaglesham, 1981;Haystead and Marriott, 1978;Ledgard et al, 1985;Ta and Faris, 1988), or indirect transfer via mineralisation of senescing clover roots and nodules (Haynes, 1986;Henzell, 1972;Walker, 1956). There is also evidence from 15N studies that N is released from the root-nodule system (Ruschel et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…This response period occurred in both experiments, even though Experiment 1 took place earlier in the growing season than Experiment 2. The increased accumulation of N in sorghum grown in mixed culture during this period may be associated with Leucaena exudation of fixed N and/or root and nodule decomposition as suggested by Ta and Faris (1988) for N transfer from alfalfa (Medicago sativa) to timothy (Phleum pratense).…”
Section: Discussionmentioning
confidence: 99%